The Historical Novel - Lukacs Georg (Merlin Press, 1989)
Preface, Foreword, The Classical Form of the Historical Novel, Historical Novel and Historical Drama, The Historical Novel and the Crisis of Bourgeois Realism, The Historical Novel of Democratic Humanism, Index of Names and Authors' Works.
Preface, Foreword, The Classical Form of the Historical Novel, Historical Novel and Historical Drama, The Historical Novel and the Crisis of Bourgeois Realism, The Historical Novel of Democratic Humanism, Index of Names and Authors' Works.